The Impact of the Expository Method on Biology Learning Activities and Outcomes in Class XI - Risnawati; Firdaus Daud; Halimah Husain; Muhiddin Palennari; Muhammad Arsyad (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to examine the effect of a structured expository teaching method on students’ learning activities and biology learning outcomes. A quasi-experimental design was employed involving two grade XI classes at SMA Negeri 1 Monta in the 2025/2026 academic year (N = 60 students). The experimental class received a systematically organized expository approach emphasizing clear explanation, guided practice, and feedback, while the control class was taught using routine teacher-centered instruction without structured stages. Data were collected through observation, pretest–posttest assessments, questionnaires, and documentation, and analyzed using descriptive statistics, MANOVA, and N-Gain analysis. The results showed that the experimental class achieved higher mean scores in learning activities (77.59) and learning outcomes (posttest = 88.63) compared to the control class. The N-Gain score of the experimental class (g = 0.67) indicated moderate effectiveness, higher than the control class (g = 0.47). MANOVA results confirmed a significant simultaneous effect on both dependent variables (p < 0.05). These findings suggest that the structured expository method contributes positively and moderately to improving student engagement and academic achievement when implemented systematically.